2016
DOI: 10.1103/physrevc.93.034906
|View full text |Cite
|
Sign up to set email alerts
|

Charm production in Pb + Pb collisions at energies available at the CERN Large Hadron Collider

Abstract: We study charm production in Pb+Pb collisions at √ sNN =2.76 TeV in the Parton-Hadron-StringDynamics transport approach and the charm dynamics in the partonic and hadronic medium. The charm quarks are produced through initial binary nucleon-nucleon collisions by using the PYTHIA event generator taking into account the (anti-)shadowing incorporated in the EPS09 package. The produced charm quarks interact with off-shell massive partons in the quark-gluon plasma and are hadronized into D mesons through coalescenc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
161
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 151 publications
(178 citation statements)
references
References 74 publications
13
161
1
Order By: Relevance
“…The hadronized D−mesons then interact with light hadrons in the hadronic phase until freeze out and subsequently undergoes semileptonic decay. We have found that the PHSD approach, which has been applied for charm production in Au+Au collisions at √ s NN =200 GeV [29] and in Pb+Pb collisions at √ s NN =2.76 TeV [30], describes the R AA as well as the v 2 of D−mesons in reasonable agreement with the experimental data from the STAR collaboration [33,34] and from the ALICE collaboration [35,36] when including the initial shadowing effect in the latter case.…”
Section: Introductionsupporting
confidence: 73%
See 4 more Smart Citations
“…The hadronized D−mesons then interact with light hadrons in the hadronic phase until freeze out and subsequently undergoes semileptonic decay. We have found that the PHSD approach, which has been applied for charm production in Au+Au collisions at √ s NN =200 GeV [29] and in Pb+Pb collisions at √ s NN =2.76 TeV [30], describes the R AA as well as the v 2 of D−mesons in reasonable agreement with the experimental data from the STAR collaboration [33,34] and from the ALICE collaboration [35,36] when including the initial shadowing effect in the latter case.…”
Section: Introductionsupporting
confidence: 73%
“…The dotted lines in figure 12 and 13 are, respectively, the R AA of heavy mesons and D−mesons and B−mesons at √ s NN =200 GeV. They also show that the shadowing effect is not so critical in reproducing experimental data, which is different from the LHC energies [30]. [37,38].…”
Section: Results For Heavy-ion Reactionsmentioning
confidence: 97%
See 3 more Smart Citations